The Effect Of Service Quality And Ticket Prices On Customer Satisfaction On KM Passenger Ships. Kelud Travel Route Jakarta – Medan - Kuncoro, Yahya; Putri, Diva Dhaffina Rico; Sianturi, Reni Monika (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2023)
This study aims to analyze the impact of Service Quality and Ticket Prices on Consumer Satisfaction. The research approach used is explanatory research with a focus on quantitative analysis. Data was collected through the distribution of questionnaires to consumers of PT. PELNI which uses the services of KM passenger ships. Kelud on the Jakarta-Medan travel route. The population that was the subject of the study included all users of these services, and the research sample taken amounted to 96 respondents using the Slovin Method in taking primary data through questionnaires. Data analysis was carried out through a Multiple Linear Regression approach after undergoing assumption tests on consumers and service users. From the results of testing, this study concluded that a positive and significant influence was obtained between service quality and ticket prices on the level of passenger satisfaction using the services of PT. PELNI.